Hollow FeNi@NCG Materials Prepared with a Double-template Strategy as Highly Efficient Catalysts for Rechargeable Zn-air Batteries. Issue 9 (1st September 2022) - Wang, Lu; Long, Jilan; Chen, Cheng; Gou, Xinglong
Abstract : One-step pyrolysis approach is the most common used method to synthesize the cathode catalysts of Zn-air batteries (ZABs). However, it is still a challenge to control the structural elements. Herein, a double-template strategy has been established by fabricating GO-doped porous g-C3 N4 supported FeNi-MOF arrays as templates to synthesize the FeNi@NCG-T architecture as highly efficient electrocatalysts. The obtained FeNi@NCG-T catalysts exhibit well-defined hollow architecture with directional arrangement tendency, which may be advantageous to construct a tri-phase region so as to accelerate the O2 -containing species transmission and increase the accessibility of internal active sites, thus boosting the catalytic performances and kinetics. The optimal Fe1 Ni1 @NCG-700 catalyst delivers excellent electrochemical activity with the overpotential of merely 217 mV (after iR correction) for OER (1 M KOH) and a remarkable small potential gap of 0.625 V between ORR and OER. The Fe1 Ni1 @NCG-700 based aqueous ZAB exhibits high peak power density of 210.79 mW·cm −2 and high specific capacity of 784.84 mAh·g −1 and long term charge/discharge stability. The corresponding button-shaped solid-state ZAB also presents excellent charge/discharge durability (>466 cycles) with outstanding performances. Most importantly, two as-synthesized button solid-state ZABs catalysts can afford a 2 V LED lamp over 36 h, proving the strong pratical application prospect.